Sales and Collusion in a Market with Storage. Issue 3 (1st June 2014) - Nava, Francesco; Schiraldi, Pasquale
Abstract: Sales are a widespread and well-known phenomenon documented in several product markets. This paper presents a novel rationale for sales that does not rely on consumer heterogeneity, or on any form of randomness to explain such periodic price fluctuations. The analysis is carried out in the context of a simple repeated price competition model, and establishes that firms must periodically reduce prices in order to sustain collusion when goods are storable and the market is large. The largest equilibrium profits are characterized at any market size. A trade-off between the size of the industry and its profits arises. Sales foster collusion, by magnifying the inter-temporal links in consumers' decisions.